Empowering B40 Chemical Science students: an entrepreneurial initiative in sustainable oyster mushroom cultivation / Nabilah Ismail ... [et al.] - Ismail, Nabilah; Mat Nasir, Siti Nur Sumaiyyah; Anak Flora, Elisa Subang; Ros Azley, Nadiah Hanis; Ariffin, Arzaimiruddin (2024)
This project focuses on empowering B40 Chemical Science students to engage in entrepreneurship through the cultivation and sale of oyster mushrooms in between classes. The initiative involves training students in the cultivation and sale of oyster mushrooms on campus, providing a practical and sustainable business model that can be managed alongside their academic commitments. Addressing key challenges such as limited space, financial constraints, and lack of support, the program offers a comprehensive module covering mushroom cultivation techniques, financial management, and effective marketing strategies. Emphasis is placed on sustainable practices to ensure minimal environmental impact, with sales commissions awarded based on participant performance. The primary objectives are to generate additional income for students, enhance their entrepreneurial skills, and raise awareness of sustainable development goals. By fostering community involvement and continuous improvement, the project seeks to cultivate a resilient and environmentally conscious entrepreneurial mindset among university students.